2013
DOI: 10.3390/ijms14024242
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Nanotechnology

Abstract: Nanotechnology is a multidisciplinary field that covers a vast and diverse array of devices and machines derived from engineering, physics, materials science, chemistry and biology. These devices have found applications in biomedical sciences, such as targeted drug delivery, bio-imaging, sensing and diagnosis of pathologies at early stages. In these applications, nano-devices typically interface with the plasma membrane of cells. On the other hand, naturally occurring nanostructures in biology have been a sour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
122
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 205 publications
(129 citation statements)
references
References 304 publications
(292 reference statements)
1
122
0
2
Order By: Relevance
“…All classes of emulsifiers (with respect to charge and molecular weight) can be used to stabilize the lipid dispersion. It has been found that an emulsifier combination may prevent particle agglomeration more efficiently [27]. The lipid NPs combine the advantages of lipid emulsion and polymeric NPs while overcoming the temporal and in vivo stability issues that trouble the conventional and nanoscale delivery approaches [28].…”
Section: Novel Delivery Modalitiesmentioning
confidence: 99%
“…All classes of emulsifiers (with respect to charge and molecular weight) can be used to stabilize the lipid dispersion. It has been found that an emulsifier combination may prevent particle agglomeration more efficiently [27]. The lipid NPs combine the advantages of lipid emulsion and polymeric NPs while overcoming the temporal and in vivo stability issues that trouble the conventional and nanoscale delivery approaches [28].…”
Section: Novel Delivery Modalitiesmentioning
confidence: 99%
“…[4,15,16] The use of lipid-based carriers is further beneficial to research on siRNA delivery because it has been demonstrated that encapsulating RNA with lipids not only decreases the degradation rates of the RNA but also increases cellular uptake of the nucleic acid material. [19] However, even though there have been many advances in developing lipid-based carriers for delivery, their introduction and application into clinical practice has been slow partly due to problems in pharmaceutical manufacturing as well as regulations set out by the government. [23] …”
Section: Lipid-based Vectorsmentioning
confidence: 99%
“…These networks can be designed to perform useful tasks. Lipids and surfactants are typically used to prevent the merging of the contacting droplets [75]. Despite being thin, bilayers form robust interfaces, allowing for flexible network architectures.…”
Section: Droplet-based Micro and Nanotechnologymentioning
confidence: 99%